2013
DOI: 10.1002/fam.2216
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fire behaviour of high‐speed trains' interior materials: small‐scale and full‐scale fire tests

Abstract: SUMMARY The development of fire‐safety measures for high‐speed passenger trains has been focused on preventing fire initiation or delaying fire growth and spread through small‐scale tests of the materials used in trains. However, new fire‐safety approaches for trains consider a systemic approach. This approach considers numerous global factors that influence fire dynamics, such as the influence of vehicle design, selection of materials, and active and passive protection systems installed. In the present paper,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In a follow‐on study, Capote et al compared cone calorimeter test data of wall, ceiling, and seat materials with that measured in the previous study by NIST . A large‐scale test inside a portion of an actual railcar was performed using a backpack as an ignition source (35–45 kW fire) with the location of the source changed in the 4 tests conducted.…”
Section: Scientific Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a follow‐on study, Capote et al compared cone calorimeter test data of wall, ceiling, and seat materials with that measured in the previous study by NIST . A large‐scale test inside a portion of an actual railcar was performed using a backpack as an ignition source (35–45 kW fire) with the location of the source changed in the 4 tests conducted.…”
Section: Scientific Literaturementioning
confidence: 99%
“…In a follow-on study, Capote et al 30 researchers explored the size of the ignition source required to cause the railcar to reach flashover as well as the contribution of passenger personal items to causing flashover. With a sufficiently large initiating fire (300-400 kW), the presence of the passenger personal items resulted in a fire that caused the railcar section to reach flashover producing a 3.2-MW fire.…”
Section: Standard Room-corner Fire Testingmentioning
confidence: 99%
“…A detailed review [10] of rail fire performance standards, large train fire incidents, recent experiments on flashover train fires, surveys of design fires used in the past and existing design fire estimation methods were reported. Updated works on train car fires [11][12][13][14][15][16][17] are summarized. Design fire is a crucial and decisive parameter to predict room fire development in performance-based design on fire safety provisions.…”
Section: Introductionmentioning
confidence: 99%
“…These research programmes involved small-, medium- and real-scale fire tests, but also, the combination of small-scale and full-scale test has been used to analyse the fire behaviour of interior materials of high-speed trains. 5 In addition, the influence of the ignition source location in different compartment sizes and configurations has been analysed by Parkes and Fleischmann, 6 and it has been found that these parameters significantly influence fire development.…”
Section: Introductionmentioning
confidence: 99%